Speciation and mobility of arsenic and antimony in soils and mining wastes from an abandoned Sb–Au mining area. (May 2023) - Drahota, Petr; Venhauerova, Petra; Strnad, Ladislav
Abstract: Gold mining activities have long been recognized as one of the most important local sources of arsenic (As) and antimony (Sb). While the environmental impact of As is documented in the literature from many mining regions worldwide, still little data is available concerning the environmental chemistry and associations of Sb. Here, we used bulk analyses, selective extractions, X-ray diffraction, electron microprobe, and Raman microspectrometry to determine and compare the distribution, speciation, and mobility of As and Sb in three historical mining wastes and two soil profiles at the Krásná Hora-Milešov and Příčovy Sb–Au ore districts (Czech Republic). The mining wastes were slightly alkaline, with both high and variable concentrations of As (318–1360 mg/kg) and Sb (214–8740 mg/kg). The naturally developed soils were acidic to neutral and enriched in As (up to 208 mg/kg) as well as in Sb (up to 255 mg/kg), with the highest concentrations in the arable topsoil (≤40 cm). In the mining wastes, the primary ore minerals (arsenopyrite, pyrite, and stibnite) have been substantially oxidized and replaced by secondary As and Sb mineral phases such as Fe (hydr)oxides, Ca–Fe–Sb (hydr)oxides, as well as the less common Ca–Sb (hydr)oxides and Ca–Fe arsenates. The primary sulfide minerals were absent in the soils, and both As and Sb were particularly bound to crystalline Fe (hydr)oxides (goethite and hematite) and clay minerals (especially true for Sb). The leaching of As and Sb from all the samples with water was pH-dependent and relatively low, as less than 2.1% of the total As and Sb contents in the samples had been released. Water-extractable concentrations were usually below 30 μg/L for As and 450 μg/L for Sb, except for an alkaline and As- and Sb-rich mining wastes, which released up to 1500 μg/L of As and 5400 μg/L of Sb. Interaction of agricultural soils with low PO4 3− indicated that As was more likely mobilized by the addition of low PO4 3− (0.1 mM) than Sb was. Although the water extraction data mostly documented the higher mobility of Sb compared to As, the addition of low PO4 3− into agricultural soils strongly increases As mobility. Based on the results of this study, leaching of As and Sb from mining wastes by rainwater can contribute to the dispersion of these metalloids and a potential hazard for the surrounding environments. Highlights: As and Sb in the mining wastes are bound to Ca–Fe–Sb and Ca–Sb (hydr)oxides. As and Sb in the soils are sequestered by Fe (hydr)oxides and clay minerals. Mobility of As is lower compared to Sb due to the higher sorption efficiency of As. Low phosphate levels (0.1–10 mmol) only enhance mobility of As.